Program Transformasi Perpustakaan Berbasis Inklusi Sosial (Studi Kasus di Dinas Perpustakan dan Kearsipan Kabupaten Padang Pariaman) - Agustin, Serlina; Primadesi, Yona (ARZUSIN, 2024)
This research aims to describe the Social Inclusion-Based Library Transformation Program at the Archives and Library Office of Padang Pariaman Regency based on connectivity, content, and human aspects. This type of research is qualitative research using descriptive methods. There are 2 informants in this study consisting of 1 first expert librarian and 1 young expert librarian. Data collection techniques were carried out by interview, observation and documentation methods. Data analysis techniques were carried out in three stages, namely data reduction, data presentation and conclusion drawing. Based on the results of the research conducted, it shows that the Social Inclusion-Based Library Transformation Program is based on three aspects, namely. (1) Connectivity aspect: infrastructure facilities for people with disabilities; efforts to reach out to users have not been carried out effectively; and the OPAC library material search system that does not function properly. (2) Content Aspect, there is no collection for people with disabilities; and library socialization to the community has not been carried out thoroughly. (3) Human Aspect: the community is less responsive; budget limitations; and the partnership network with various parties is not yet widespread. The efforts made by the Office of Archives and Libraries of Padang Pariaman Regency in overcoming obstacles are to establish partnerships with village library managers.